Motivational Techniques, Communication Patterns, and Job Productivity of Non-Academic Staff in Ogun State Owned Universities of Nigeria - Adeyemi, Muyiwa; Adetunji, A.; Ositoye, Wale (NIU Journal of Social Sciences, 2019)
This study seeks to find out whether motivational techniques and communication pattern relatively and collectively affect employees productivity. Six (6) hypotheses were tested for this purpose. The descriptive survey design was employed in investigating the aforementioned correlates. The population of study included 1496 and 486 non- academic staff of Olabisi Onabanjo University (Ago- Iwoye) and Tai- Solarin University of Education (Ijagun) respectively. A sample of some 299 and 97 staff were respectively selected from these two schools for questionnaire administration. The simple percentage and correlation statistics were employed in analyzing the responses of the entire 396 sample who responded to the 32 questionnaire items. The results obtained showed very strong correlation between the understudied factors. It was, therefore, recommended that care should be taken in choosing the appropriate motivational techniques and communication patterns if the expected levels of employee outputs have to be achieved. Choosing and applying the right motivational techniques and communication pattern will produce the best results in any given employee. Keywords : University Education Motivational Techniques, Communication Patterns, Job Productivity and Influence Rate